2009
DOI: 10.1017/s1355617709991007
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive reserve as a moderator of postconcussive symptoms in children with complicated and uncomplicated mild traumatic brain injury

Abstract: The occurrenceof postconcussive symptoms (PCS) following mild traumatic brain injury (TBI) in children may depend on cognitive reserve capacity. This prospective, longitudinal study examined whether the relationship between mild TBI and PCS is moderated by cognitive ability, which served as a proxy for cognitive reserve. Participants included 182 children with mild TBI and 99 children with orthopedic injuries (OI), ranging from 8 to 15 years of age when injured. Mild TBI were classified as complicated (n = 32)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 158 publications
(133 citation statements)
references
References 33 publications
6
125
1
1
Order By: Relevance
“…15 The injuries were classified as mild, moderate, or severe, based on CDC 16 and World Health Organization (WHO) 17 definitions and 1 functioning at 24 h after injury. Because mild TBI patients are a heterogeneous group, 18,19 we subdivided these children into three subgroups: the Mild I group were children who had a normal initial head CT scan or had no scan, the Mild II group were children who had a skull fracture but no intracranial hemorrhage on CT scan, and the Mild III group had intracranial hemorrhage on CT.…”
Section: Methodsmentioning
confidence: 99%
“…15 The injuries were classified as mild, moderate, or severe, based on CDC 16 and World Health Organization (WHO) 17 definitions and 1 functioning at 24 h after injury. Because mild TBI patients are a heterogeneous group, 18,19 we subdivided these children into three subgroups: the Mild I group were children who had a normal initial head CT scan or had no scan, the Mild II group were children who had a skull fracture but no intracranial hemorrhage on CT scan, and the Mild III group had intracranial hemorrhage on CT.…”
Section: Methodsmentioning
confidence: 99%
“…Socioeconomic status has been associated with cognitive reserve, and research has shown that persons with higher cognitive reserve are less susceptible to cognitive deficits after TBI. [51][52][53] The theory of cognitive reserve posits that an individual's experiences affect the efficiency of their neural and cognitive networks, such that those with enriching life histories are protected against cognitive decline.…”
Section: Rabinowitz Et Almentioning
confidence: 99%
“…In the United States alone, the rate of TBI-related emergency department visits was over 500 per 100,000 for children less than 17 years of age (Faul et al, 2010), and 75% of these injuries were classified as mild in nature (Centers for Disease Control and Prevention, 2003). While the majority of mild TBI (mTBI) patients fully recover within the first several months of injury (Babikian and Asarnow, 2009;Satz et al, 1997), a small subset of patients may experience persistent neurocognitive or psychosocial dysfunction for years (Anderson et al, 2001;Babikian et al, 2011;Catale et al, 2009;Fay et al, 2010;McKinlay et al, 2002McKinlay et al, ,2009McKinlay et al, ,2010Sterr et al, 2006), or even decades (Daneshvar et al, 2011;Hessen et al, 2007;Klonoff et al, 1993). Thus it is critical to identify neuroimaging and behavioral markers sensitive to mTBI to better understand recovery, and to prevent potentially long-term adverse outcomes from repeated mTBI.…”
Section: Introductionmentioning
confidence: 99%